A single dose of ketamine cannot prevent protracted stress-induced anhedonia and neuroinflammation in rats. (2nd January 2022) - Moraga-Amaro, Rodrigo; Guerrin, Cyprien G. J.; Reali Nazario, Luiza; Lima Giacobbo, Bruno; J. O. Dierckx, Rudi A.; Stehberg, Jimmy; de Vries, Erik F. J.; Doorduin, Janine
Abstract: Worldwide, millions of people suffer from treatment-resistant depression. Ketamine, a glutamatergic receptor antagonist, can have a rapid antidepressant effect even in treatment-resistant patients. A proposed mechanism for the antidepressant effect of ketamine is the reduction of neuroinflammation. To further explore this hypothesis, we investigated whether a single dose of ketamine can modulate protracted neuroinflammation in a repeated social defeat (RSD) stress rat model, which resembles features of depression. To this end, male animals exposed to RSD were injected with ketamine (20 mg/kg) or vehicle. A combination of behavioral analyses and PET scans of the inflammatory marker TSPO in the brain were performed. Rats submitted to RSD showed anhedonia-like behavior in the sucrose preference test, decreased weight gain, and increased TSPO levels in the insular and entorhinal cortices, as observed by [ 11 C]-PK11195 PET. Whole brain TSPO levels correlated with corticosterone levels in several brain regions of RSD exposed animals, but not in controls. Ketamine injection 1 day after RSD disrupted the correlation between TSPO levels and serum corticosterone levels, but had no effect on depressive-like symptoms, weight gain or the protracted RSD-induced increase in TSPO expression in male rats. These results suggest that ketamine does not exert its effect on the hypothalamic–pituitary–adrenal axis by modulation of neuroinflammation.